Evaluation of antidiabetic, antioxidant, and cytotoxic potential of maize (zea mays l.) husk leaf extracts - Riaz, Muhammad; Nawaz, Sadia; Ilyas, Iqra; Rehman, Muhammad Misbah ur; Qadir, Rahman; Mehmood, Tahir; Afzal, Muhammad; Abdul Rehman, Natasha; Ali, Abid (Cellular and Molecular Biology, 2021)
In current study, Maize (Zea mays L.) husk leave extracts were appraised for biological activities such as cytotoxicity, antidiabetic, antioxidant and antimicrobial. Maceration was performed to collect various fractions of husk leave extracts using a pool of solvents i.e., n-hexane, chloroform, ethyl acetate, butanol and methanol. Antioxidant potential was measured by 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging, reducing power and linoleic acid oxidation assay, using butylated hydroxy toluene (BHT) as a positive control. Total phenolic and flavonoid contents were found to be 18.47-425.11 mg/100 g GAE and 5.83-16.72 mg/100 g CE, respectively. The DPPH scavenging assay was exhibited in the range of 76.36 to 88.53%. The percentage inhibition in linoleic acid oxidation was found from 10.16 to 79.51%. Significant antimicrobial activity was demonstrated by husk leaf extracts against bacterial strains and fungal strains using disc diffusion and minimum inhibitory concentration (MIC) method. Amylase alpha assay was employed to analyze the antidiabetic activity which ranged between 9.52-24.81%. Cytotoxicity was evaluated by % age lysis (0.35-9.54%), while thrombolytic activity ranged between 7.67 to 31.27%. The results presented in this study revealed that maize (Zea mays L.) husk leaf extracts can be a valuable source of biologically active compounds and may be consumed as a source of potent herbal medicine in pharmaceuticals.